One Pot Synthesis of Nanofiber-Coated Magnetic Composites as Magnetic Dispersive Solid-Phase Extraction Adsorbents for Rapid Determination of Tetracyclines in Aquatic Food Products - Li, Peipei; Bai, Junlu; He, Pengfei; Zeng, Junjie (Molecules (Basel, Switzerland), 2023)
A magnetic adsorbent based on a C-nanofiber (Fe3O4@C–NFs) nanocomposite was synthesized using a simple one-pot co-precipitation method. The characterized results showed that the obtained C–nanofiber–coated magnetic nanoparticles had many attractive features such as a large specific surface area and a highly interwoven and branched mesoporous structure, as well as distinguished magnetism. The nanocomposite was then used as an adsorbent in the magnetic solid phase extraction (MSPE) of four typical tetracyclines (oxytetracycline, tetracycline, chlortetracycline, and doxycycline) in aquatic products. The TCs in the extract were determined using ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS). Experimental variables of MSPE, including the sorbent amount, pH condition, adsorption and desorption time, and desorption solvent, were investigated and optimized systematically. The method validation indicated that the developed method showed good linearity (R2 > 0.995) in the range of 1.0–200 ng/mL. The average recoveries at the spiked levels ranged from 90.7% to 102.7% with intra-day and inter-day relative standard deviations (RSDs, n = 6) ranging from 3.72% to 8.17% and 4.20% to 9.69%, respectively. The limit of detection (LOD) and limit of quantification (LOQ) for the four kinds of TCs were 0.7 μg/kg and 2.0 μg/kg, respectively. Finally, MSPE based on C-nanofiber-coated magnetic nanoparticles was successfully applied to TC analysis in real aquatic products (grass carp, large yellow croaker, snakehead, mandarin fish, Penaeus vannamei, swimming crab, etc.). Compared with traditional extraction methods, the proposed method for TC analysis in aquatic products is more sensitive, effective, recyclable, and environmentally friendly.